Mal de Mar: a reading of Jorge de Sena’s “A Grã-Canária” in (trans-) Atlantic transit - Gonçalves Miranda, Rui (Tagus Press (New England University Press), 2014)
This article analyzes Jorge de Sena’s short story “A Grã-Canária” in the context of a wider discussion on the topographies of the South Atlantic taken as an ideological construct, to some extent always already textual(ized). The story emphasizes the tensions in the enclosing of either the boat or the island as spaces of absolute fascist rule (in 1938 and 1961), and its setting in the Atlantic allows for a wider criticism of oppressive regimes operating in the South Atlantic axis while also addressing the “Atlantic exception” (Roberto Vecchi) in the context of wider European headings. It dismantles both the incipient establishing of the Atlantic as a “Portuguese Sea” by the Estado Novo and the construction of the legal and political conceptions such as that of the “overseas provinces” in the Constitutional Revision of 1951. This reading aims to foreground the spacing (Jacques Derrida) intrinsic to the inscription of such topographies of otherness and the projection of the selfsame in order to stress the tensions, the contradictions, and the limits of discourses underwriting an “immunitary paradigm” (Roberto Esposito) bent on establishing and marking the borders between a supposed self and its projected others.